2022
DOI: 10.15294/kemas.v17i3.28692
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Healthy Housing and TB Prevalence in Yogyakarta City

Abstract: Environmental health is one of the determinants factors toward the public health status. Transmission of tuberculosis (TB) is influenced by environmental factors. Based on previous TB data in local study, it shows that urban areas (urban) have a high case rate. Therefore, this study aims to reveal the disparity of urban TB sufferers, especially in the city of Yogyakarta based on indicators of the physical environment of the house from the coverage of healthy households. The method of study used is quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The home environment as a residence for tuberculosis patients plays a role in the health index. 10,11 Furthermore, it can be used as an effort to prevent transmission to other family members. 12,13 It also helps in healing as planned or worsens the patient's condition.…”
Section: Discussionmentioning
confidence: 99%
“…The home environment as a residence for tuberculosis patients plays a role in the health index. 10,11 Furthermore, it can be used as an effort to prevent transmission to other family members. 12,13 It also helps in healing as planned or worsens the patient's condition.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control research in Pamekasan Regency found that a healthy housing condition can reduce the incidence of pulmonary TB up to 35 times (Wahyudi et al, 2018). Other researches have also assessed the relationship between the occupants' density, ventilation, air temperature, humidity, and the incidence of pulmonary TB disease (Marbun, 2022;Musfirah et al, 2022;Siregar et al, 2022;Syamsuddin et al, 2020). Sutomo (2013) found that dense residential areas, inadequate ventilation, inappropriate air temperature, and the absence of natural lighting in Banjarmasin, South Kalimantan housing increase the risk of developing pulmonary TB up to 2.2 times, 14.44 times, 13.14 times, and 17.54 times, respectively.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…The internal environment is a state of mental processes in the individual's body (in the form of experience, emotional abilities, and personality) and procedures that trigger biological stressors (cells and molecules) from within the individual's body. The external environment can be in the form of physical, chemical, or pathological conditions or factors that are accepted by the individual and perceived as a threat [12][13][14].…”
Section: The Physical Home Environment and The Event Of Tuberculosismentioning
confidence: 99%
“…Environmental health includes all physical, chemical, and biological factors affecting health [12]. Several factors become the risk of tuberculosis, one of which is the physical environment of the house, such as ventilation area, occupancy density, light intensity, type of house floor humidity, and temperature [13,14].…”
Section: Introductionmentioning
confidence: 99%